Age and metastasis – How age influences metastatic spread in cancer. Colorectal cancer as a model. (April 2022) - Pretzsch, E.; Nieß, H.; Bösch, F.; Westphalen, C.B.; Jacob, S.; Neumann, J.; Werner, J.; Heinemann, V.; Angele, M.K.
Abstract: Metastasis is the major cause of death in cancer patients. Whereas colorectal cancer (CRC) incidence increases with age, metastatic spread seems to decline. Furthermore, the epidemiology of CRC is changing. There is an increase in CRC incidence in the young, presenting at an advanced stage with higher likelihood of synchronous or metachronous metastases, and a decline in CRC incidence and metastatic spread in the oldest-old. Emerging data suggest that age-related changes with regard to tumor biology (e.g. genomic instability), the tumor microenvironment (e.g. inflammaging) and the immune system (e.g. immunosenescence), complemented by interaction between the genome and exposome might contribute to the observed metastatic patterns. As aging is a key prognostic factor, this highlights the need for further studies investigating age-related patterns and underlying mechanisms of tumor growth and dissemination. Eventually, this might allow for better risk stratification, refinement of screening strategies and follow-up care as well as therapies tailored to reflect patient age and that might possibly target responsible biomarkers in a precision medicine approach. This review aims to discuss the influence of aging on metastatic spread in colorectal cancer and elucidate underlying mechanisms responsible for the observed metastatic patterns. Highlights: Colorectal cancer incidence increases with age whereas metastatic spread declines. Age-related changes in primary tumor and microenvironment drive metastatic spread. Aging impacts metastasis via changes in tumor biology, inflammaging, immunosenescence.